Prognostic and clinicopathological value of Ki-67/MIB-1 expression in renal cell carcinoma: a meta-analysis based on 4579 individuals - Wang Z (Cancer Management and Research, 2017)
Zhun Wang, Hui Xie, Linpei Guo, Qiliang Cai, Zhiqun Shang, Ning Jiang, Yuanjie Niu Department of Urology, Tianjin Institute of Urology, The Second Hospital of Tianjin Medical University, Tianjin, China Background: Previous studies have investigated the prognostic significance of Ki-67/MIB-1 expression in renal cell carcinoma (RCC), however, the reports are controversial and inconsistent. This study aimed to investigate Ki-67/MIB-1 expression in RCC and its correlation with prognosis and clinicopathological features.Methods: We searched relevant studies that reported associations between Ki-67/MIB-1 expression and prognosis in RCC from PubMed, Embase, Web of Science, and Cochrane Library studies published until April 14, 2017. Hazard ratios (HRs) and 95% confidence intervals (CIs) were extracted from eligible studies. Fixed and random effects models were used to calculate pooled HRs and 95% CIs according to heterogeneity.Results: A total of 4579 participants from 23 eligible studies were included in this analysis. The results showed that Ki-67/MIB-1 expression was associated with poor overall survival (HR=2.06, 95% CI: 1.64–2.57) and cancer specific survival (HR=2.01, 95% CI: 1.66–2.44). In addition, Ki-67/MIB-1 expression was also correlated with TNM stage (III/IV vs I/II: OR=1.92, 95% CI: 1.61–2.28), pathological T stage (pT3/pT4 vs pT1/pT2: OR=1.56, 95% CI: 1.21–2.02), distant metastasis (M1 vs M0: OR=1.81, 95% CI: 1.34–2.43), and Fuhrman grade (III/IV vs I/II: OR=1.94, 95% CI: 1.21–3.10).Conclusion: Our study demonstrates that the presence of high Ki-67/MIB-1 expression and advanced clinicopathological features were correlated with poor prognosis in RCC patients. Keywords: Ki-67/MIB-1, renal cell carcinoma, prognosis, meta-analysis